Functional Profiling Identifies Determinants of Arsenic Trioxide Cellular Toxicity. (25th January 2019) - Sobh, Amin; Loguinov, Alex; Yazici, Gulce Naz; Zeidan, Rola S; Tagmount, Abderrahmane; Hejazi, Nima S; Hubbard, Alan E; Zhang, Luoping; Vulpe, Chris D
Abstract: Arsenic exposure is a worldwide health concern associated with an increased risk of skin, lung, and bladder cancer but arsenic trioxide (As III ) is also an effective chemotherapeutic agent. The current use of As III in chemotherapy is limited to acute promyelocytic leukemia (APL). However, As III was suggested as a potential therapy for other cancer types including chronic myeloid leukemia (CML), especially when combined with other drugs. Here, we carried out a genome-wide CRISPR-based approach to identify modulators of As III toxicity in K562, a human CML cell line. We found that disruption of KEAP1, the inhibitory partner of the key antioxidant transcription factor Nrf2, or TXNDC17, a thioredoxin-like protein, markedly increased As III tolerance. Loss of the water channel AQP3, the zinc transporter ZNT1 and its regulator MTF1 also enhanced tolerance to As III whereas loss of the multidrug resistance protein ABCC1 increased sensitivity to As III . Remarkably, disruption of any of multiple genes, EEFSEC, SECISBP2, SEPHS2, SEPSECS, and PSTK, encoding proteins involved in selenocysteine metabolism increased resistance to As III . Our data suggest a model in which an intracellular interaction between selenium and As III may impact intracellular As III levels and toxicity. Together this work revealed a suite of cellular components/processes which modulate the toxicity of As III in CML cells. Targeting such processes simultaneously with As III treatment could potentiate As III in CML therapy.